2021
DOI: 10.1017/s0031182021001967
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of Leishmania parasites isolated from visceral and cutaneous leishmaniasis patients

Abstract: Leishmaniasis is an infectious disease in which different clinical manifestations are classified into three primary forms: visceral, cutaneous and mucocutaneous. These disease forms are associated with parasite species of the protozoan genus Leishmania. For instance, Leishmania infantum and Leishmania tropica are typically linked with visceral (VL) and cutaneous (CL) leishmaniasis, respectively; however, these two species can also cause other form to a lesser extent. What is more alarming is this characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…It is reported that the influx of 1.5 million Syrian refugees in Lebanon has elevated the CL incidence significantly (13). For Turkey, in addition to the rise in CL incidence, especially in the early years of the influx of Syrian citizens due to civil war, a new Leishmania genotype (Syrian/Turkish Leishmania tropica population structure) with two sub-populations was just shown for the first time, by multilocus microsatellite typing studies on clinical isolates of Leishmania species within the country (14)(15)(16).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that the influx of 1.5 million Syrian refugees in Lebanon has elevated the CL incidence significantly (13). For Turkey, in addition to the rise in CL incidence, especially in the early years of the influx of Syrian citizens due to civil war, a new Leishmania genotype (Syrian/Turkish Leishmania tropica population structure) with two sub-populations was just shown for the first time, by multilocus microsatellite typing studies on clinical isolates of Leishmania species within the country (14)(15)(16).…”
mentioning
confidence: 98%
“…This may be due to the modifications in the proteome in Hatay isolates of L. infantum, shown by the proteomic analyses. Factors listed above that influence leishmaniasis in the world -global warming, deforestation, and the refugee crisis -may all contribute to the emergence of hybrid and clinically-modified Leishmania strains (5,(9)(10)(11)15). Another good example of how new Leishmania genotypes influence the local infection profiles is the identification of the rare MON-58 zymodeme in Crete (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation